Kontrak Karya PT Freeport Indonesia dalam Perspektif Pancasila dan UUD NRI 1945 - Redi, Ahmad (Jurnal Konstitusi, 2016)
PT Freeport Indonesia (PT FI) has a Contract of Work (KK) to undertake mining materials in Grasberg and Ertsberg mining areas which has begun in 1967 and will end in 2021. Since the promulgation of Law No. 4 of 2009 on Mineral and Coal Mining (UU Minerba), regulation on mineral and coal undertaking has been in accordance with Pancasila (State Ideology) and the 1945 Constitution, however, because UU Minerba can only be effective for legal actions after its promulgation therefore items related to KK before the existence of that law cannot be regulated. On the other hand, the existence of KK of PT FI is considered to be in violation with Pancasila namely The Fifth Principle “Social Justice for The Whole People of Indonesia”, and Article 33 (3) of 1945 Constitution concerning the substance of land, water, and natural wealth ‘shall be controlled by the State’ and ‘for maximum use for people’s welfare’. This article shall discuss on whether KK of PT FI has been in accordance with Pancasila and the1945 Constitution? And what should Government do in order KK of PT FI can be regulated within the frame of Pancasila and the 1945 Constitution? The method used in this writing is juridical normative. Based on the writer’s analysis, KK of PT FI is violating Pancasila and the 1945 Constitution. The effort to adjust it to Pancasila and the 1945 Constitution shall be conducted through renegotiation of KK of PT FI based on “hardship” principle in UNIDROIT Principles of International Commercial Contracts and principle of natural resources for national interest and people’s welfare in the Resolution of General Assembly Resolution 1803 (XVII) of 14 December 1962, “Permanent Sovereignty Over Natural Resources.